Physical abuse and neglect among 13-15 year old children of migrant mothers in Kandy district. - Jayasinghe, W.A.D.S (My University, 2005)
A cross sectional study compared randomly selected 850 children (index group) between the ages of 13-15 years whose mothers were employed abroad with similar group of children who were living with their mothers. The data were analyzed using the chi square and other non parametric tests. In the index group the grandmother is now the primary caregiver. As reported by the children Jin the index group the care provided by the main caregiver was inferior to the quality of care given by the mother. The prevalence of severity of the outcome following physical abuse was higher among children in the index group. But mild forms physical abuse like smacking (hitting by hand) are higher among children in the comparison group . All the children who dropped out from the school (n =25) were from the index group . The types and frequency of physical abuse ( corporal punishment) in the schools were higher among the children from the index group . Poor school performances and behavioral 1 problems in the schools were significantly higher in the index group. This study shows the adverse consequences on the children’s behaviour as well as on school performances. It is known that adults with history of abuse in childhood, may in turn abuse children later . Therefore abuse and neglect of children of the next generation may happen as proven in other studies. It appears that the negative impact outweigh the financial benefits. Therefore cost effectiveness of maternal migration for employment needs to be assessed in a future study.